Effect of species, breeds, season and stage of lactation on urea content of milk and its variation during processing of milk and milk products - Patel, Hiteshkumar Dahyabhai (Indian Journal of Dairy Science, 2019)
The aim of this study was assessing the urea level in milk of different species and its breeds, effect of season, stage of lactation and its relationship with fat, SNF and milk yield as well as to investigate changes in urea content during various processing treatments of milk and milk products. Pooled samples of buffaloes (Murrah) and cows (Tharparkar, Sahiwal and Karan Fries) were collected and estimated the naturally present urea over a period of ten days. Average urea content in milk of Murrah, Tharparkar, Sahiwal and Karan Fries was found to be 41.38, 40.85, 38.2 and 25.53mg/100 ml, respectively. Urea content in milk was influenced by season and it was observed that significantly higher values in winter and lower in summer and intermediate values in rainy season of both species. During stage of lactation, milk urea observed significantly lower in colostrum of Sahiwal and Murrah than normal milk but maximum observed during 2nd-3rd month of lactation. During stage of lactation, negative relationship was observed between urea, fat and SNF content, whereas positive relationship was observed between urea and milk yield. Processing treatments of milk significantly affected the urea level. During Pasteurization (63Â°C/30 min) and boiling (2 to 5 min) of milk, urea level was increased, whereas during sterilization (121Â°C/15 min), urea level was decreased. The average urea content in dahi, khoa, skim milk powder (roller dried), paneer and paneer whey was found to be 18.78, 184.60, 408, 1.67 and 40.67 mg/100 g, respectively.